Differences in ACTN3, ACE, and ADBR3 polymorphisms between Croatian National Team and non-national team elite soccer players - Ruzic, L.; Radman, I.; Matkovic, B. R. (Baltic Journal of Health and Physical Activity, 2023)
Introduction: This study investigated the differences in ACTN3, ACE and ADRB3 variants in top-level soccer players who entered the Croatian National Team and the ones who did not but played for two best Croatian teams.